Artisanal mining versus sustainability of agricultural food supply chains: effects of the conflicts in Southern Zimbabwe. Issue 3 (3rd April 2022) - Chari, Felix; Novukela, Cawe; Ngcamu, Bethuel Sibongiseni
ABSTRACT: This article seeks to establish the social and environmental consequences of artisanal mining on economic sustainability of agricultural food supply chains in Zimbabwe. Following a descriptive research design, interviews were conducted with 36 farmers. Interviewees were purposively sampled from potential respondents in Southern Zimbabwe. Interview results were triangulated with data from published reports and newspaper articles. Data was analysed using NVivo application version 12, and presented in vignettes. The results of this study are useful to artisanal miners, farmers, and government. Recommendations for further studies are given.